Land use and management effects on soil organic matter fractions in Rohid Ferralsols and Haplic Arenosols in Bindura and Shamva districts in Zimbabwe - Mujuru, Lizzie; Mureva, A; Velthorst, E.J.; Hoosbeek, M.R. (Elsevier, 2013)
Soil organic carbon (SOC) is a major attribute of soil quality that responds to land management activities which is also important in the regulation of global carbon (C) cycling. This study evaluated bulk soil C and nitrogen (N) contents and C and N dynamics in three soil organic matter (SOM) fractions separated by density. The study was based on three tillage systems on farmer managed experiments (conventional tillage (CT), ripping (RP), direct seeding (DS)) and adjacent natural forest (NF) in Haplic Arenosols (sandy) and Rhodic Ferralsols (clayey) of Zimbabwe. Carbon stocks were significantly larger in forests than tillage systems, being significantly lower in sandy soils (15 and 14 Mg C ha− 1) than clayey soils (23 and 21 Mg C ha− 1) at 0–10 and 10–30 cm respectively. Nitrogen content followed the same trend. At the 0–10 cm depth, SOC stocks increased under CT, RP and DS by 0.10, 0.24, 0.36 Mg ha− 1 yr− 1 and 0.76, 0.54, 0.10 Mg ha− 1 yr− 1 on sandy and clayey soils respectively over a four year period while N stocks decreased by 0.55, 0.40, 0.56 Mg ha− 1 and 0.63, 0.65, 0.55 Mg ha− 1 respectively. SOM fractions were dominated by mineral associated heavy fraction (MaHF) which accounted for 86–93% and 94–98% on sandy and clayey soils respectively. Tillage systems on sandy soils had the smallest average free light fraction (fLF) and occluded light fraction (oLF) C stocks (25.3 ± 1.3 g m− 2 and 7.3 ± 1.2 g m− 2) at 0–30 cm when compared with corresponding NF (58.4 ± 4 g m2 and 18.5 ± 1.0 g m− 2). Clayey soils, had the opposite, having all fLF C and N in tillage systems being higher (80.9 ± 12 g C m− 2 and 2.7 ± 0.4 g N m− 2) than NF (57.4 ± 2.0 g C m− 2 and 2.4 ± 0.3 g N m− 2). Results suggest that oLF and MaHF C and N are better protected under DS and RP where they are less vulnerable to mineralisation while fLF contributes more in CT. Thus, DS and RP can be important in maintaining and improving soil quality although their practicability can be hampered by unsupportive institutional frameworks. Under prevailing climatic and management conditions, improvement of residue retention could be a major factor that can distinguish the potential of different management practices for C sequestration. The exploitation of the benefits of RP or DS and the corresponding sustainability of systems need support for surface cover retention which should also be extended to conventional tillage.